ANALYSIS OF STEGANOGRAPHIC METHODS IN DCT DOMAIN - Vladimír HAJDUK; Martin DZIAK; Miroslav VOZŇÁK; Dušan LEVICKÝ (Acta Electrotechnica et Informatica, 2017)
The main role of steganalysis is a successful detection of secret communication. This communication is exclusively created by steganography. Steganographic methods deals with hiding a secret information into any type of multimedia data, for example to static images. Among basic requirements to steganographic systems belongs the perceptual transparency. Inserted information is perceptually transparent if an average subject is unable to distinguish any difference between data before and after embedding process. Nevertheless, each steganographic method necessarily causes some change in some statistical parameter. It represents the basis for building a successful steganalyzer. In this article are tested the impact of four steganographic methods to the selected statistical parameters which are usually utilized in the image objective quality assessment. Specifically, peak signal-to-noise ratio, normalized cross correlation, a local histogram of DCT coefficients and sample variance. The contribution of the article consists in the usage of results in the theory of statistical vector creation in building the particular image steganalytic method.